The Microbial Landscape of Sea Stars and the Anatomical and Interspecies Variability of Their Microbiome - Jackson, Elliot W.; Pepe-Ranney, Charles; Debenport, Spencer J.; Buckley, Daniel H.; Hewson, Ian (Frontiers in Microbiology, 2018)
Sea stars are among the most important predators in benthic ecosystems worldwide which is partly attributed to their unique gastrointestinal features and feeding behaviors. Despite their ecological importance, the microbiome of these animals and its influence on adult host health and development largely remains unknown. To begin to understand such interactions we sought to understand what bacteria are associated with these animals, how the microbiome is partitioned across regions of the body and how seawater influences their microbiome. We analyzed the microbiome composition of a geographically and taxonomically diverse set of sea star taxa by using 16S rRNA gene amplicon sequencing and compared microorganisms associated with different regions of their body and to their local environment. In addition, we estimated the bacterial and coelomocyte abundance in the sea star coelomic fluid and bacterioplankton abundance in the surrounding seawater via epifluorescence microscopy. The average bacterial cell abundance observed in the coelomic fluid was one to two orders of magnitude lower than the bacterioplankton abundance in the surrounding seawater suggesting a selection against the presence of microorganisms in the coelomic fluid. The sea star microbiome was also significantly different from seawater with relatively few shared microbial taxa. Microbial communities were found to be significantly different between the pyloric caeca, gonads, coelomic fluid, and body wall of the animals. The most noticeable difference between anatomical sites was the greater relative abundance of Spirochaetae and Tenericutes found in hard tissues (gonads, pyloric caeca, and body wall) than in the coelomic fluid. The microbiome of sea stars thus appears to be anatomically partitioned, distinct from the microbial community of seawater and contains a relatively low abundance of bacteria within the coelomic cavity.